2017
DOI: 10.1002/bip.22981
|View full text |Cite
|
Sign up to set email alerts
|

Stereodependent and solvent‐specific formation of unusual β‐structure through side chain‐backbone H‐bonding in C4(S)‐(NH2/OH/NHCHO)‐L‐prolyl polypeptides

Abstract: It is shown that C4(S)-NH /OH/NHCHO-prolyl polypeptides exhibit PPII conformation in aqueous medium, but in a relatively hydrophobic solvent trifluoroethanol (TFE) transform into an unusual β-structure. The stereospecific directing effect of H-bonding in defining the specific structure is demonstrated by the absence of β-structure in the corresponding C4(S)-guanidinyl/(NH/O)-acetyl derivatives and retention of β-structure in C4(S)-(NHCHO)-prolyl polypeptides in TFE. The distinct conformations are identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Conformation vs Morphology. The observed β-structure in TFE for the cis-4-substituted L/D-prolyl polypeptides correlates well with the self-assembly of these peptides into nanofibers 24,25,30 as seen from the FESEM images. The polypeptides with the PPII form assemble into irregular or spherical nanostructures (Figures 8A,D and 9A,C) in buffer.…”
Section: Effect Of Concentration On Morphology Of L C -Ampsupporting
confidence: 69%
“…Conformation vs Morphology. The observed β-structure in TFE for the cis-4-substituted L/D-prolyl polypeptides correlates well with the self-assembly of these peptides into nanofibers 24,25,30 as seen from the FESEM images. The polypeptides with the PPII form assemble into irregular or spherical nanostructures (Figures 8A,D and 9A,C) in buffer.…”
Section: Effect Of Concentration On Morphology Of L C -Ampsupporting
confidence: 69%
“…Since β‐strand structure is the least stabilized owing to the carbonyl‐carbonyl interactions, the β‐contribution in the absence of an alternative stabilizing force seems very unlikely. For example, isomerization of some model oligoproline‐based structure into the β‐like antiparallel sheets was reported in nonpolar media, when this was assisted by backbone‐side chain hydrogen bond formation, but not otherwise . Thus, the CD curves in the oligo‐Oic sequences can be attributed to dominating P II helix, which is encapsulated in a hydrophobic shell and is still sensitive to the presence of the polar groups in the solvent via the secondary effects .…”
Section: Discussionmentioning
confidence: 99%
“…The latter were documented only very recently for peptides formed by specific proline analogues. [35][36][37]…”
Section: Hydrophobic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can also be manipulated with the substitution pattern in proline [55,56]. Moreover, it was recently shown that the oligoproline scaffold can also adopt a special type of a β-structure in case of certain chemical analogues [57,58].…”
Section: The Proline Worldmentioning
confidence: 99%